2009
DOI: 10.1016/j.ydbio.2009.08.027
|View full text |Cite
|
Sign up to set email alerts
|

The type I BMP receptors, Bmpr1a and Acvr1, activate multiple signaling pathways to regulate lens formation

Abstract: BMPs play multiple roles in development and BMP signaling is essential for lens formation. However, the mechanisms by which BMP receptors function in vertebrate development are incompletely understood. To determine the downstream effectors of BMP signaling and their functions in the ectoderm that will form the lens, we deleted the genes encoding the type I BMP receptors, Bmpr1a and Acvr1, and the canonical transducers of BMP signaling, Smad4, Smad1 and Smad5. Bmpr1a and Acvr1 regulated cell survival and prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 44 publications
5
91
0
Order By: Relevance
“…The preliminary results indicate that cell proliferation before E11.5 is likely to be mediated by MAPK1/3-independent pathways (data not shown). It has been shown that BMP/activinactivated signals are essential for cell proliferation during early lens development (Rajagopal et al, 2009). Additionally, our results indicated that loss of both MAPK1 and MAPK3 in the lens drastically reduced cell proliferation throughout the entire epithelial layer at E14.5 (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…The preliminary results indicate that cell proliferation before E11.5 is likely to be mediated by MAPK1/3-independent pathways (data not shown). It has been shown that BMP/activinactivated signals are essential for cell proliferation during early lens development (Rajagopal et al, 2009). Additionally, our results indicated that loss of both MAPK1 and MAPK3 in the lens drastically reduced cell proliferation throughout the entire epithelial layer at E14.5 (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…During nervous system development, conditional inactivation of Smad1 and Smad5 resulted in cerebellar hypoplasia, reduced granule cell numbers, and disorganized Purkinje neuron migration during embryonic development, whereas conditional inactivation of Smad4 produced only very mild cerebellar defects (10). Furthermore, during lens development, cell death occurred associated with inactivation of Smad1/5, but not with inactivation of Smad4 (12). In addition, Smad1 and Smad5 have been proven essential for bone development, but inactivation of Smad4 led to only minor bone defects (42).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other systems have shown that inhibition of Bmp signaling in the epithelium causes cells to shorten and become columnar or cuboidal (Eom et al, 2011;Gibson and Perrimon, 2005;Rajagopal et al, 2009;Shen and Dahmann, 2005). However, dorsomorphin treatment does not cause widespread columnar conversion; epithelium above the merged clusters is columnar, while epithelium between these clusters remains pseudostratified (Fig.…”
Section: Modulation Of Bmp Signaling Affects Cluster Formation and Pamentioning
confidence: 95%